The Impact of Pharmacists’ Interventions to Prevent Medication Errors at a Tertiary Hospital in Central Jakarta, Indonesia - Azrifitria Azrifitria; Siti Fauziyah; Apriliana Nur (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2019)
To promote the safety and quality of pharmaceutical services are still an issue in Indonesia. One way of doing so is to implement pharmaceutical care standards and prevent medication errors. The aim of this study was to evaluate if the intervention that conducts before and after the socialization in the standard of pharmacy service could cause a decrease in medication errors. The study was conducted by using a quasi-experimental design without a control group in outpatient pharmacy services of a tertiary hospital in central Jakarta, Indonesia. A total of 7627 prescriptions were collected prospectively by the total sampling method in April and May 2016. The observation was conducted in two stages of prescribing and dispensing. A total of 2541 medication errors identified, error rates of 16%  and 33.3%  were found during the prescribing and dispensing stages before socialization (April 2016), respectively. After the socialization in May 2016, the error rates of 15.2% and 20.2% were found in the prescribing and dispensing stages, respectively. However, the differences pre- and post-socialization were not significant (p>0.05). The greatest decrease in medication error was found on drug labels, which fell from 721(21%) to 458 (11%). Observations on near-miss events based on a risk matrix showed that these were dominated by a low-degree of risk. Based on these results, it could be concluded that the intervention given to pharmacists could decline medication errors. Nevertheless, further study with a greater amount of time and better pharmacist socialization is required.